A study on the characteristics of a novel inorganic solidified foam for the prevention and control of the spontaneous combustion of coal. (12th September 2022) - Xue, Di; Hu, Xiangming; Liang, Yuntao; Sun, Gongzheng; Tang, Hui; Wang, Wei
Graphical abstract: Highlights: Response surface methodology was used to optimize formulation of solidified foam. Mechanism of foaming and curing reaction of NICF was clarified. Rice husk ash with high pozzolanic activity replaced fly ash. Core parameters of the mixing device were determined by numerical simulations. Abstract: The spontaneous combustion of coal seriously threatens the safe operation of coal mines. In order to solve the problems of the traditional inorganic solidified foam (TICF), i.e., a long gelation time, difficulty in uniform mixing, and low efficiency for blocking air leakage, a novel inorganic solidified foam (NICF) was proposed in this study to prevent the spontaneous combustion of coal; it was prepared by using rice husk ash (RHA), xanthan gum (GX), and sodium silicate (WG) as modifiers. Plackett-Burman experiments and response surface methodology were used to optimize the expansion ratio, stability coefficient, and gelation time of NICF and to determine the formulation of NICF in order to achieve rapid sealing of air leakage channels. A spiral hollow mixing device (SHMD) was developed based on the characteristics of NICF. The mixing effect of an aqueous foam (AF) and compound seriflux (CS) was numerically simulated by the ANSYS FLUENT software, and the SHMD parameters were determined with a high expansion ratio and uniform mixing of grout. The mechanism of the foaming and curing reaction of NICF and its mechanism for preventing the spontaneous combustion of coal were obtained by means of scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). The experimental results indicated that WG hydrolyzed to produce an orthosilicic acid sol and sodium hydroxide in the process of particle hydration, and the sol could bind the particles to the hydration products. In addition, WG dissociated to generate a large amount of orthosilicate ions ([SiO4 ] 4- ), which combined with the calcium ions present in a high concentration on the surface of the hydrated particles; this considerably reduced the gelation time of NICF. Ca 2+ on the surface of the hydrated particles chelated with the active functional groups such as the hydroxyl and carboxyl groups in GX, improving the compressive strength of NICF in the initial hydration stage. Compared with fly ash, rice husk ash has higher pozzolanic activity, and it undergoes a secondary hydration reaction with numerous calcium hydroxide crystals, increasing the hydration degree. This study can provide a theoretical basis for reducing the gelation time of NICF and explaining its foaming and curing reaction mechanism.